Economizing Nonlocal Resource in Two-Way Remote Preparations of Inequivalent Quantum States Under a Common Control - An, Nguyen Ba (Communications in Physics, 2021)
A recently proposed protocol for two parties to securely and simultaneouslyexchange inequivalent quantum states under the same control of a third party [Int. J. Theor. Phys. (2020); https://doi.org/10.1007/s10773-020-04657-0] is revisited. It is shown in this paper that the required tasks are equally well accomplished with a nonlocal resource which is greatly economized by rationally exploiting local resources. Furthermore, the economized nonlocal resource with appropriate local operations on local resources also allows exchanging inequivalent states other than those previously considered.